EVALUATION OF FLIGHT QUALITY BY RVSM, PBN, CATII, CATIII STANDARDS BASED ON NIKULIN MODIFIED CRITERION - L. O. Marasanov (Научный вестник МГТУ ГА, 2018)
Flight operations with the use of standards Reduced Vertical Separation Minimum (RVSM); Performance-based Navigation (PBN); auto landings on CATII CATIII ICAO categories have become common practices in relation to the relevant requirements of ICAO. In this case, operators should receive special operational permits, due to that the task of determining the feasibility of such operations became operational. Increasing the reliability requirements to estimate the accuracy characteristics quality of flight operations requires the development and improvement of methods for their evaluation. First of all, the application of methods based on more accurate representations of error models with more correct models of the error probability density distribution is required, especially in the field of large, rare errors. This article solves one of the tasks of this complex approach to estimate the accuracy characteristics – the task of processing flight information in order to determine the estimates of the accuracy characteristics of the flight-navigation complex (FNC), since the problem solving provides the possibility of obtaining an integral estimate of the accuracy characteristics based on the application of combined methods. It is shown that the power of the Nikulin criterion is almost twice as high as the Pearson power criterion, which in some cases excludes the acceptance of incorrect hypotheses about the form of the hypothetical distribution function. The use of Nikulin criterion makes it possible to significantly improve the assessments accuracy of flight quality performance characteristics according to RVSM, PBN, CATII and CATIII standards by increasing the criterion power. It significantly increases the estimates accuracy of the accuracy characteristics obtained during the deciphering of flight information.